Boom, bust, and beyond : new perspectives on the 1720 stock market bubble - Condorelli, Stefano; Menning, Daniel (De Gruyter Oldenbourg, 2019)
Few financial crises, historically speaking, have attracted such attention as the Mississippi and South Sea Bubbles of 1719?20. The twin bubbles had major economic and political implications, sending shock waves through the whole of Europe; they astonished contemporaries, and, to a large extent, they still resonate today. This volume offers new readings of these events, drawing on fresh research and new evidence that challenge traditional interpretations. The chapters engage, in particular, with: the geographical frame of the 1719-20 bubbles their social, cultural, economic and political impact the ways in which contemporaries understood speculation the contributions and impact of a diverse array of participants popular and print memorialization of the events Overall, the volume helps to rewrite the history of the 1719?20 bubbles and to recontextualize their place within eighteenth-century history.